Compatibility and Biomineralization Oriented Optimization of Nutrient Content in Nitrate-Reducing Microbial Self-Healing Concrete - Kardogan, Beyza; Sekercioglu, Kadir; Ersan, Yusuf Cagatay (MDPI, 2021)
Microbially induced calcium carbonate precipitation (MICP) can be mentioned among the popular approaches to develop a self-healing concrete. The production of dissolved inorganic carbon through microbial activity is the main precursor for MICP in concrete and it is limited by the bioavailability of the nutrients. When nutrients are added to the mortar as admixtures, their bioavailability becomes more significant for crack repair because nutrients disperse in the mortar and considerable fraction stays far from a single crack. Therefore, the determination of bioavailability of nutrients and its variation with the initial nutrient content and crack age is essential to optimize a recipe for bacteria-based self-healing concrete. This study presents the optimum nutrient content defined for nitrate-reduction-based self-healing bioconcrete. In the tests, calcium nitrate (CN) and calcium formate (CF) were combined with a CF:CN w/w ratio of 2.50. Mortar properties and bioavailability of nutrients were analysed at different nutrient doses. Moreover, the bioavailability of nutrients at different crack ages changing between 3 and 56 days was monitored. Finally, resuscitation, microbial activity and the MICP performance of nitrate reducing biogranules were tested at defined nutrient bioavailabilties. The optimum nutrient content was determined as 7.00% (CF 5.00% and CN 2.00%). The leaching rates of formate ions were twice the leaching rate of the nitrate ions at similar initial concentrations, which led to a bioavailable HCOO-/NO3-N ratio of 23 g/g in cracked mortar. Under optimum nutrient conditions, the CaCO3 precipitation yield of nitrate reducing biogranules was recorded as 1.5 g CaCO3/g HCOO- which corresponded to 68% C precipitation efficiency.
Kardogan, Beyza/0000-0002-8227-8270; Ersan, Yusuf Cagatay/0000-0003-4128-0195
Keywords: Denitrification; Acdc; Screening; Calcium Carbonate; Setting Properties; Strength